Disturbance Intensity and Recovery Time Steer Vegetation Shifts in Subtropical Wetlands - Maidana, Carlos Emilio (2026)
Aims: Subtropical wetlands provide critical biodiversity and ecosystem services, yet increasingly face agricultural pressures. Our study assessed how disturbance type, intensity, and recovery time influence vegetation dynamics in wetlands, employing robust methodological approaches to characterize ecological responses. Location: Malezales wetlands, Corrientes, Argentina. Methods: We used a chronosequence approach based on vegetation surveys of 612 plots (1 m2 each) distributed across 43 paddocks with contrasting disturbance histories. Vegetation cover was assessed using the Braun-Blanquet phytosociological method. We evaluated three types of anthropogenic disturbances commonly associated with agricultural land use in subtropical wetlands: drainage, plowing, and rice cultivation. Multivariate analyses, specifically canonical correspondence analysis (CCA), were applied to quantify how disturbance intensity and recovery time influence plant community composition and functional group responses. Results: Recovery time accounted for up to 72% of the variation in vegetation composition. High-intensity disturbances (plowing and rice cultivation) resulted in long-term reductions in species richness, diversity, and grass cover, whereas low-intensity disturbances (drainage) facilitated partial vegetation recovery within approximately 15 years. Multivariate analyses further identified a functional shift from tall, erect grasses toward decumbent, stoloniferous species. Conclusions: Malezales wetlands exhibit substantial resilience to low-intensity agricultural disturbances but remain highly susceptible to intensive impacts that may lead to persistent alternative ecological states. Given increasing agricultural pressure on subtropical wetlands, our findings underscore the critical need for targeted conservation and restoration strategies informed by detailed ecological assessment methodologies.